An implementation method for the supervisory control of time-driven systems applied to high-voltage direct current transmission grids. (January 2019) - Romero-Rodríguez, Miguel; Delpoux, Romain; Piétrac, Laurent; Dai, Jing; Benchaib, Abdelkrim; Niel, Eric
Abstract: In recent years, the growth of renewable energy production has encouraged the development of new technologies, such as High-Voltage Direct Current (HVDC) networks, that enhance the integration of such energy sources to power transmission grids. However, this type of technology introduces new challenges in the way power transmission systems are controlled and operated, as faster and more complex control strategies will be needed in a domain which nowadays relies heavily on human decisions. In this context, Discrete Event Systems (DES) modeling and Supervisory Control Theory (SCT) are powerful tools for the development of a supervisory control to be deployed in the grid. This paper presents an application of the SCT to HVDC grids and proposes an implementation method for the resulting supervisors. The proposed method is capable of integrating decentralized and discrete-event controllers that interact with the continuous-time physical system. The language chosen for the implementation is C code, as it can be easily incorporated in power system simulation software, such as EMTP-RV. The method is validated by the simulation of the start-up of a point-to-point link in the EMTP-RV software. Highlights: The controller is separated into different levels of detail, can be decentralized. The controller interacts with a continuous-time physical system. The controller is implemented in C code in power system simulation software.